Creating a Long-Term Diabetic Rabbit Model. (6th December 2010) - Wang, Jianpu; Wan, Rong; Mo, Yiqun; Zhang, Qunwei; Sherwood, Leslie C.; Chien, Sufan
Abstract : This study was to create a long-term rabbit model of diabetes mellitus for medical studies of up to one year or longer and to evaluate the effects of chronic hyperglycemia on damage of major organs. A single dose of alloxan monohydrate (100 mg/kg) was given intravenously to 20 young New Zealand White rabbits. Another 12 age-matched normal rabbits were used as controls. Hyperglycemia developed within 48 hours after treatment with alloxan. Insulin was given daily after diabetes developed. All animals gained some body weight, but the gain was much less than the age-matched nondiabetic rabbits. Hyperlipidemia, higher blood urea nitrogen and creatinine were found in the diabetic animals. Histologically, the pancreas showed marked beta cell damage. The kidneys showed significantly thickened afferent glomerular arterioles with narrowed lumens along with glomerular atrophy. Lipid accumulation in the cytoplasm of hepatocytes appeared as vacuoles. Full-thickness skin wound healing was delayed. In summary, with careful management, alloxan-induced diabetic rabbits can be maintained for one year or longer in reasonably good health for diabetic studies.